Astegolimab (anti-ST2) efficacy and safety in adults with severe asthma: A randomized clinical trial - Kelsen, Steven G.; Agache, Ioana O.; Soong, Weily; Israel, Elliot; Chupp, Geoffrey L.; Cheung, Dorothy S.; Theess, Wiebke; Yang, Xiaoying; Staton, Tracy L.; Choy, David F.; Fong, Alice; Dash, Ajit; et al. (Journal of allergy and clinical immunology, 2021)
The IL-33/ST2 pathway is linked with asthma susceptibility. Inhaled allergens, pollutants, and respiratory viruses, which trigger asthma exacerbations, induce release of IL-33, an epithelial-derived “alarmin.” Astegolimab, a human IgG2 mAb, selectively inhibits the IL-33 receptor, ST2. Approved biologic therapies for severe asthma mainly benefit patients with elevated blood eosinophils (type 2-high), but limited options are available for patients with low blood eosinophils (type 2-low). Inhibiting IL-33 signaling may target pathogenic pathways in a wider spectrum of asthmatics. This study evaluated astegolimab efficacy and safety in patients with severe asthma. This double-blind, placebo-controlled, dose-ranging study (ZENYATTA [A Study to Assess the Efficacy and Safety of MSTT1041A in Participants With Uncontrolled Severe Asthma]) randomized 502 adults with severe asthma to subcutaneous placebo or 70-mg, 210-mg, or 490-mg doses of astegolimab every 4 weeks. The primary endpoint was the annualized asthma exacerbation rate (AER) at week 54. Enrollment caps ensured ∼30 patients who were eosinophil-high (≥300 cells/μL) and ∼95 patients who were eosinophil-low (<300 cells/μL) per arm. Overall, adjusted AER reductions relative to placebo were 43% (P = .005), 22% (P = .18), and 37% (P = .01) for 490-mg, 210-mg, and 70-mg doses of astegolimab, respectively. Adjusted AER reductions for patients who were eosinophil-low were comparable to reductions in the overall population: 54% (P = .002), 14% (P = .48), and 35% (P = .05) for 490-mg, 210-mg, and 70-mg doses of astegolimab. Adverse events were similar in astegolimab- and placebo-treated groups. Astegolimab reduced AER in a broad population of patients, including those who were eosinophil-low, with inadequately controlled, severe asthma. Astegolimab was safe and well tolerated. [Display omitted]